Time Travels for People on Earth are Already Possible - Antonov, A. A. (European Journal of Applied Sciences, 2025)
The article argues that the version of the special theory of relativity (SRT), which is generally recognised and studied in all physics textbooks, is incorrect. And numerous proofs are given to it. SRT on the one hand and all radio engineering, electrical engineering and computer technology on the other hand mutually refute each other. SRT is also refuted by the existence of resonance and shock oscillations. I.e. if SRT were true, then neither computers, nor mobile phones and smartphones, nor television, nor GPS trackers, nor pianos and other musical instruments should exist, nor even tsunamis should not exist and swings on children's playgrounds should not swing after a push from parents. Consequently, to refute SRT it was not necessary to invent some very expensive experiments on Tevatron and Large Hadron Collider. It was not necessary after detection of Cherenkov radiation [1] to correct SRT. And it was necessary simply to look around and to understand that the generally recognised version of SRT is refuted by numerous all known and therefore irrefutable natural and created by people processes. And, hence, SRT should be corrected. Therefore the author has created the corrected version of SRT, from which relativistic formulas and new scientific knowledge received after creation of incorrect version of SRT it followed that in the nature there is not only our visible universe, but besides it there are many other mutually invisible universes and antiverse. And besides existing in universes of matter, space and time, in antiverses there exist antimatter, anti-space and anti-time. And the existence of anti-time makes travelling in space possible not only in space but also in time. And the article explains how it can be done now.